Painting & decorating - Butterfield, Derek (Wiley-Blackwell, 2011)
This textbook presents a series of concise, simply written and well illustrated technical information sheets, providing essential job knowledge and understanding for the painter and decorator. It gives thorough coverage of materials and equipment both decorative and industrial currently in use, and gives useful guidance on specification